Current imaging of childhood urinary infections: prospective survey. Issue 6828 (14th March 1992) - Rickwood, A. M.; Carty, H. M.; McKendrick, T.; Williams, M. P.; Jackson, M.; Pilling, D. W.; Sprigg, A.
Abstract : OBJECTIVES–To assess whether ultrasonography alone is adequate for routine screening of childhood urinary infection, whether clinical features determine the need for further investigations, and which investigations are most appropriate. DESIGN–Prospective survey of children with proved urinary infection and a preinvestigation record of clinical features. Ultrasonography and intravenous urography were routine, with choice of further studies determined by ultrasonographic findings. SETTING–A children's hospital and two district general hospitals in Mersey region. MAIN OUTCOME MEASURES–Sensitivity and specificity of ultrasonography both generally and in relation to clinical features. Accuracy of intravenous urography compared with radioisotope examinations. RESULTS–Specificity of ultrasonography was good (99% (95% confidence interval 96% to 100%)) but sensitivity modest (43% (32% to 55%)), principally with respect to detecting vesicoureteric reflux and renal scarring. Among older children (aged 2-10 years) with positive ultrasound results and fever or vomiting the sensitivity in detecting reflux (with and without renal scarring) was 78% (62% to 89%) and the specificity 69% (60% to 78%); in detecting renal scarring (with and without reflux) the sensitivity was 100% (80% to 100%) and specificity 65% (56% to 74%). Renal scarring and obstructive uropathies were better assessed by radioisotope examinations than by intravenous urography. CONCLUSIONS–Ultrasonography alone is inadequate for routine screening of childhood urinary infection. Though further investigations remain advisable in infants, in older children they can be restricted to a minority who have positive ultrasound examinations or have had fever or vomiting. Radioisotope examinations largely eliminate the need for intravenous urography.